# 99 questions/Solutions/70

### From HaskellWiki

(submit my own solution) |
|||

Line 116: | Line 116: | ||

Tree> runP (parse df) "afg^^c^bd^e^^^" | Tree> runP (parse df) "afg^^c^bd^e^^^" | ||

Just (Node 'a' [Node 'f' [Node 'g' []],Node 'c' [],Node 'b' [Node 'd' [],Node 'e' []]],"") | Just (Node 'a' [Node 'f' [Node 'g' []],Node 'c' [],Node 'b' [Node 'd' [],Node 'e' []]],"") | ||

+ | </haskell> | ||

+ | |||

+ | ---- | ||

+ | |||

+ | A more naive solution, trying to split the string with stack | ||

+ | <haskell> | ||

+ | stringToTree :: String -> Tree Char | ||

+ | stringToTree (x:xs@(y:ys)) | ||

+ | | y == '^' = Node x [] | ||

+ | | otherwise = Node x (map stringToTree subs) | ||

+ | where subs = snd $ foldl parse ([],[]) $ init xs | ||

+ | parse ([],[]) z = ([z], [[z]]) | ||

+ | parse (stack, acc) z = (stack', acc') | ||

+ | where stack' | ||

+ | | z == '^' = init stack | ||

+ | | otherwise = stack ++ [z] | ||

+ | acc' = if stack == [] | ||

+ | then acc ++ [[z]] | ||

+ | else (init acc) ++ [(last acc) ++ [z]] | ||

+ | </haskell> | ||

+ | |||

+ | It's more direct to convert Tree back to string | ||

+ | <haskell> | ||

+ | treeToString :: Tree Char -> String | ||

+ | treeToString (Node x ts) | ||

+ | = [x] ++ concatMap treeToString ts ++ "^" | ||

</haskell> | </haskell> |

## Revision as of 00:51, 1 February 2012

(**) Tree construction from a node string.

We suppose that the nodes of a multiway tree contain single characters. In the depth-first order sequence of its nodes, a special character ^ has been inserted whenever, during the tree traversal, the move is a backtrack to the previous level.

By this rule, the tree below (`tree5`) is represented as: `afg^^c^bd^e^^^`

Define the syntax of the string and write a predicate tree(String,Tree) to construct the Tree when the String is given. Make your predicate work in both directions.

We could write separate printing and parsing functions, but the problem statement asks for a bidirectional function.

First we need a parser monad, with some primitives:

newtype P a = P { runP :: String -> Maybe (a, String) } instance Monad P where return x = P $ \ s -> Just (x, s) P v >>= f = P $ \ s -> do (x, s') <- v s runP (f x) s' instance MonadPlus P where mzero = P $ \ _ -> Nothing P u `mplus` P v = P $ \ s -> u s `mplus` v s charP :: P Char charP = P view_list where view_list [] = Nothing view_list (c:cs) = Just (c, cs) literalP :: Char -> P () literalP c = do { c' <- charP; guard (c == c') } spaceP :: P () spaceP = P (\ s -> Just ((), dropWhile isSpace s))

Next a `Syntax` type, combining printing and parsing functions:

data Syntax a = Syntax { display :: a -> String, parse :: P a }

(We don't use a class, because we want multiple syntaxes for a given type.) Some combinators for building syntaxes:

-- concatenation (<*>) :: Syntax a -> Syntax b -> Syntax (a,b) a <*> b = Syntax { display = \ (va,vb) -> display a va ++ display b vb, parse = liftM2 (,) (parse a) (parse b) } -- alternatives (<|>) :: Syntax a -> Syntax b -> Syntax (Either a b) a <|> b = Syntax { display = either (display a) (display b), parse = liftM Left (parse a) `mplus` liftM Right (parse b) } char :: Syntax Char char = Syntax return charP literal :: Char -> Syntax () literal c = Syntax (const [c]) (literalP c) space :: Syntax () space = Syntax (const " ") spaceP iso :: (a -> b) -> (b -> a) -> Syntax a -> Syntax b iso a_to_b b_to_a a = Syntax { display = display a . b_to_a, parse = liftM a_to_b (parse a) }

The last one maps a syntax using an isomorphism between types. Some uses of this function:

-- concatenation, with no value in the first part (*>) :: Syntax () -> Syntax a -> Syntax a p *> q = iso snd ((,) ()) (p <*> q) -- list of a's, followed by finish list :: Syntax a -> Syntax () -> Syntax [a] list a finish = iso toList fromList (finish <|> (a <*> list a finish)) where toList (Left _) = [] toList (Right (x, xs)) = x:xs fromList [] = Left () fromList (x:xs) = Right (x, xs)

Now we can define the syntax of depth-first presentations:

df :: Syntax (Tree Char) df = iso toTree fromTree (char <*> list df (literal '^')) where toTree (x, ts) = Node x ts fromTree (Node x ts) = (x, ts)

We are using the isomorphism between `Tree a` and `(a, [Tree a])`.
Some examples:

Tree> display df tree5 "afg^^c^bd^e^^^" Tree> runP (parse df) "afg^^c^bd^e^^^" Just (Node 'a' [Node 'f' [Node 'g' []],Node 'c' [],Node 'b' [Node 'd' [],Node 'e' []]],"")

A more naive solution, trying to split the string with stack

stringToTree :: String -> Tree Char stringToTree (x:xs@(y:ys)) | y == '^' = Node x [] | otherwise = Node x (map stringToTree subs) where subs = snd $ foldl parse ([],[]) $ init xs parse ([],[]) z = ([z], [[z]]) parse (stack, acc) z = (stack', acc') where stack' | z == '^' = init stack | otherwise = stack ++ [z] acc' = if stack == [] then acc ++ [[z]] else (init acc) ++ [(last acc) ++ [z]]

It's more direct to convert Tree back to string

treeToString :: Tree Char -> String treeToString (Node x ts) = [x] ++ concatMap treeToString ts ++ "^"